PENERAPAN METODE DIRECTED READING ACTIVITY (DRA) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PADA MATAKULIAH KOMUNIKASI PEMERINTAHAN DI PRODI ILMU PEMERINTAHAN UIN STS JAMBI - Suryawahyuni Latief; YULFI ALFIKRI NOER (Yayasan Literasi Kita Indonesia, 2020)
The major purpose of this study is to improve the critical thinking of undergraduate student in a government communication field, UIN STS Jambi. The subject of this study was undergraduate students in semester VA in academic 2018/2019. The instruments used in this study was the last report of student results, observation paper, and a text reading with a title